2022
DOI: 10.3389/fimmu.2022.1032783
|View full text |Cite
|
Sign up to set email alerts
|

Optimized ventilation strategy for surgery on patients with obesity from the perspective of lung protection: A network meta-analysis

Abstract: ObjectivesNew ventilation modes have been proposed to support the perioperative treatment of patients with obesity, but there is a lack of consensus regarding the optimal strategy. Therefore, a network meta-analysis update of 13 ventilation strategies was conducted to determine the optimal mode of mechanical ventilation as a protective ventilation strategy decreases pulmonary atelectasis caused by inflammation.MethodsThe following databases were searched: MEDLINE; Cochrane Library; Embase; CINAHL; Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…In a recent prospective study, there was no correlation between PPCs and age, smoking history, comorbidities, type of resection, of for major cervicofacial surgery patients [7]. The lung protection ventilatory protocol for obese patients in general is reported to be more efficient with volume-controlled ventilation and individualized positive-end expiratory pressure [8]. Additionally, recently it has been reported that total intravenous anesthesia with propofol might also have a protective pulmonary effect on cervicofacial cancer surgery [9], but some methodological issues in this recent study necessitate further investigations.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent prospective study, there was no correlation between PPCs and age, smoking history, comorbidities, type of resection, of for major cervicofacial surgery patients [7]. The lung protection ventilatory protocol for obese patients in general is reported to be more efficient with volume-controlled ventilation and individualized positive-end expiratory pressure [8]. Additionally, recently it has been reported that total intravenous anesthesia with propofol might also have a protective pulmonary effect on cervicofacial cancer surgery [9], but some methodological issues in this recent study necessitate further investigations.…”
Section: Discussionmentioning
confidence: 96%
“…Adopting an intraoperative lung-protective mechanical ventilation combining a volume-controlled inverse ratio ventilation and individualized PEEP after the recruitment maneuvre may be an effective strategy to improve lung function and oxygenation [2,10,15]. DP [4] and MP [3] should be adopted in the context of lung-protective mechanical ventilation [2] to optimize the ventilatory management of Class 3 obesity patients in any stage of robotic gynecological surgery.…”
Section: Discussionmentioning
confidence: 99%